2015
DOI: 10.4049/jimmunol.1402310
|View full text |Cite
|
Sign up to set email alerts
|

Copy Number Variations in CTNNA3 and RBFOX1 Associate with Pediatric Food Allergy

Abstract: Food allergy is a significant public health concern, especially among children. Previous candidate gene studies suggested a few susceptibility loci for food allergy, but no study investigated the contribution of copy number variations (CNVs) to food allergy on a genome-wide scale. To investigate the genetics of food allergy, we performed CNV assessment using high-resolution genome-wide single nucleotide polymorphism arrays. CNV calls from a total of 357 cases with confirmed food allergy and 3980 controls were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
22
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 21 publications
(23 citation statements)
references
References 54 publications
1
22
0
Order By: Relevance
“…In this study, the CNV locus was located in the first intron of the KCNIP1 gene. Previous studies reported that the first intron may affect the mRNA stability and RNA splicing, which could significantly alter the gene function, and change cellular response to specific targets [36,37]. The further analyses did show marked positive associations of risk copy numbers in the KCNIP1 gene with attenuated insulin and accelerated glucose level, which is consistent with the physiological role of the KCNIP1 gene in adjusting insulin secretion [38].…”
Section: Discussionsupporting
confidence: 74%
“…In this study, the CNV locus was located in the first intron of the KCNIP1 gene. Previous studies reported that the first intron may affect the mRNA stability and RNA splicing, which could significantly alter the gene function, and change cellular response to specific targets [36,37]. The further analyses did show marked positive associations of risk copy numbers in the KCNIP1 gene with attenuated insulin and accelerated glucose level, which is consistent with the physiological role of the KCNIP1 gene in adjusting insulin secretion [38].…”
Section: Discussionsupporting
confidence: 74%
“…[25] CNVs can be detected by array technology, such as array comparative genomic hybridization (aCGH) and SNP arrays, as well as whole exome or whole genome sequencing which is currently under rapid development. It has showed by numerous genetic studies that CNVs are associated with various complex diseases, such as autism [26], Attention Deficit Hyperactivity Disorder (ADHD) [27], congenital heart disease [28], amyotrophic lateral sclerosis [29], obesity [30], endometriosis [31], and food allergy [32].…”
Section: Copy Number Variation (Cnv) Studymentioning
confidence: 99%
“…We also identified five GWAS with either food or peanut allergy as an outcome. Four of these were carried out in children, and the other was carried out in a population across the ages of 1‐93 years …”
Section: Resultsmentioning
confidence: 99%